PENGARUH PROGRAM MAKAN BERGIZI GRATIS (MBG) BAGI KINERJA EMITEN PAKAN TERNAK (FEEDMILL) DI PASAR MODAL INDONESIA - In'am Widiarma (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
Research on the Free Nutritious Meal Program (MBG) is particularly interesting because it is a strategic national public policy during President Prabowo Subianto's administration. It is a long-term fiscal and social investment policy. It aims to improve public nutrition, particularly for children, students, and pregnant and lactating mothers. However, this cannot be seen solely from its output; food supplies must also be adequate, particularly for chicken and egg food, which are the mainstays of the MBG. The animal feed sector, as an unavoidable supporter of the supply chain, requires the integrated capabilities of animal feed companies to determine the availability of raw materials for food in the MBG, especially chicken and eggs. Therefore, it is necessary to assess the performance of animal feed companies listed on the IDX, such as JPFA, CPIN, MAIN, and SIPD, through an evaluation of their financial reports, revenue and profit, and quarterly stock price movements. The research method used is quantitative, referring to statistical techniques such as the Mann-Whitney Test and Path Analysis, to determine whether there are significant differences in medians between groups and to test causal relationships. The results of this study indicate that the MBG program had no significant impact on revenue and profits for animal feed companies. However, MBG did increase share prices. This positive signal stems from the positive sentiment surrounding information and prospects for animal feed companies.